ASSESSMENT OF THE MANAGEMENT OF WAREHOUSING PROCESSES IN A MANUFACTURING COMPANY USING THE WERK EFFICIENCY MODEL - Macienė, Jurgita; Pilvinis, Andrius; Balvočiūtė, Rasa (PROFESSIONAL STUDIES: Theory And Practice, 2023)
The article examines the possibilities of evaluating the management of warehousing processes of a manufacturing company using the WERK efficiency model. It has been established that assessment models based on quantitatively determined indirect indicators, which can be calculated and interpreted in different ways, are mostly used in scientific works and practice. The assessment model used in the study includes more direct indicators, which by comparing them with the reference values of the best practice allow to better identify problems in the management of warehousing processes and monitor changes in this activity.